Boosting the Photoactivity of Grafted Titania: Ultrasound‐Driven Synthesis of a Multi‐Phase Heterogeneous Nano‐Architected Photocatalyst. (30th September 2020) - Giannakoudakis, Dimitrios A.; Qayyum, Abdul; Łomot, Dariusz; Besenhard, Maximilian O.; Lisovytskiy, Dmytro; Bandosz, Teresa J.; Colmenares, Juan Carlos
Abstract: The herein presented low‐power high‐frequency (500 kHz) ultrasound‐assisted precipitation synthesis (LPHF‐US) leads to a unique multiphase nano‐structured titanium dioxide, grafted with oxygen‐containing organic functionalities. The material exhibits a high porosity (surface area 326 m 2 g −1 and total pores volume 0.484 cm 3 g −1 ) and heterogeneous surface chemistry. In the used LPHF‐US synthetic protocol, the energy‐demanding calcination step leading to crystallization is eliminated and an organic residue is simultaneously grafted to the surface. That organic residue affects the anatase nanocrystals, size (4–7 nm), which are embedded in an amorphous titanium hydroxide network. This nanomaterial shows superior performance as a heterogenous photocatalyst either in a gaseous phase by decomposing toxic vapors of chemical warfare agents (a mustard‐gas surrogate), or in a liquid phase by selectively oxidizing benzyl alcohol, a model lignin‐biomass‐derived compound. The grafted organic phase enhances the catalyst's photoreactivity under visible light, by acting as a photosensitizer (antenna effect) and/or as a source of chromophores. Abstract : A new nanocatalyst consisting anatase nanocrystals (4–7 nm) in an amorphous titanium hydroxide network grafted with oxygen‐containing organic‐functionalities, is synthesized via a low‐power high‐frequency ultrasound‐assisted precipitation method. The material exhibited a high photocatalytic efficiency in decomposing toxic vapors or in the selective oxidation of benzyl alcohol. The grafted organic phase played a crucial role enriching surface features and advancing photoreactivity.